The Human Microbiome as a Focus of Antibiotic Discovery: Neisseria mucosa Displays Activity Against Neisseria gonorrhoeae - Aho, Ellen L.; Ogle, Jenie M.; Finck, Anna M. (Frontiers in Microbiology, 2020)
Neisseria gonorrhoeae infections are a serious global health problem. This organism has developed disturbing levels of antibiotic resistance, resulting in the need for new approaches to prevent and treat gonorrhea. The genus Neisseria also includes several members of the human microbiome that live in close association with an array of microbial partners in a variety of niches. We designed an undergraduate antibiotic discovery project to examine a panel of nonpathogenic Neisseria species for their ability to produce antimicrobial secondary metabolites. Five strains belonging to the N. mucosa species group displayed activity against other Neisseria in delayed antagonism assays; three of these were active against N. gonorrhoeae. The antimicrobial compound secreted by N. mucosa NRL 9300 remained active in the presence of catalase, trypsin, and HEPES buffer, and effectively inhibited a DNA uptake mutant of N. gonorrhoeae. Antimicrobial activity was also retained in an ethyl acetate extract of plate grown N. mucosa NRL 9300. These data suggest N. mucosa produces an antimicrobial secondary metabolite that is distinct from previously described antigonococcal agents. This work also serves as a demonstration project that could easily be adapted to studying other members of the human microbiome in undergraduate settings. We offer the perspective that both introductory and more advanced course-based and apprentice-style antibiotic discovery projects focused on the microbiome have the potential to enrich undergraduate curricula and we describe transferrable techniques and strategies to facilitate project design.